2009
DOI: 10.1016/j.sleep.2008.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia and its relationship to health-care utilization, work absenteeism, productivity and accidents

Abstract: This study indicates that insomnia is associated with significant morbidity in terms of health problems and health-care utilization, work absenteeism and reduced productivity, and risk of non-motor-vehicle accidents. Future studies should evaluate whether treating insomnia can reverse this morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
261
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 364 publications
(272 citation statements)
references
References 31 publications
5
261
0
6
Order By: Relevance
“…Rona et al found that, among a sample of U.K. military personnel, PTSD-related avoidance and numbing symptoms, followed by hyperarousal symptoms, were most strongly associated with poor performance at work, (e.g., less time on task, less accomplished, difficulty performing duties) [5]. Sleep disturbances have been shown to adversely affect work and academic performance, as evidenced by increased absenteeism and reduced productivity [35][36]. Fernandez-Mendoza et al showed that sleep disturbances were associated with worse neuropsychological performance on tasks involving processing speed, executive control of attention, and visual memory, all of which can affect work and academic performance [37].…”
Section: Work and Academic Performancementioning
confidence: 99%
“…Rona et al found that, among a sample of U.K. military personnel, PTSD-related avoidance and numbing symptoms, followed by hyperarousal symptoms, were most strongly associated with poor performance at work, (e.g., less time on task, less accomplished, difficulty performing duties) [5]. Sleep disturbances have been shown to adversely affect work and academic performance, as evidenced by increased absenteeism and reduced productivity [35][36]. Fernandez-Mendoza et al showed that sleep disturbances were associated with worse neuropsychological performance on tasks involving processing speed, executive control of attention, and visual memory, all of which can affect work and academic performance [37].…”
Section: Work and Academic Performancementioning
confidence: 99%
“…These costs are caused by increased health-care use, which is about three times higher among poor sleepers than among good sleepers. Most of the societal costs of insomnia (75%) stem from work absenteeism and poor work productivity (Daley et al 2009b). In total, poor sleepers cost society about 10 times more than good sleepers (Daley et al 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…These include increased risk for the metabolic syndrome, all-cause mortality, 2,3 mood and anxiety disorders, reduced productivity, accidents, and greater use of medical services. [4][5][6] A better understanding of factors contributing to insomnia could aid its prevention, which would have implications for improving function, quality of life, and long-term health.…”
mentioning
confidence: 99%